Crosslinked elastic fibers are necessary for low energy loss in the ascending aorta. (16th August 2017) - Kim, Jungsil; Staiculescu, Marius Catalin; Cocciolone, Austin J.; Yanagisawa, Hiromi; Mecham, Robert P.; Wagenseil, Jessica E.
Abstract: In the large arteries, it is believed that elastin provides the resistance to stretch at low pressure, while collagen provides the resistance to stretch at high pressure. It is also thought that elastin is responsible for the low energy loss observed with cyclic loading. These tenets are supported through experiments that alter component amounts through protease digestion, vessel remodeling, normal growth, or in different artery types. Genetic engineering provides the opportunity to revisit these tenets through the loss of expression of specific wall components. We used newborn mice lacking elastin ( Eln −/− ) or two key proteins (lysyl oxidase, Lox −/−, or fibulin-4, Fbln4 −/− ) that are necessary for the assembly of mechanically-functional elastic fibers to investigate the contributions of elastic fibers to large artery mechanics. We determined component content and organization and quantified the nonlinear and viscoelastic mechanical behavior of Eln −/−, Lox −/−, and Fbln4 −/− ascending aorta and their respective controls. We confirmed that the lack of elastin, fibulin-4, or lysyl oxidase leads to absent or highly fragmented elastic fibers in the aortic wall and a 56–97% decrease in crosslinked elastin amounts. We found that the resistance to stretch at low pressure is decreased only in Eln −/− aorta, confirming the role of elastin in the nonlinear mechanical behavior of the aortic wall. Dissipated energy with cyclic loading and unloading is increased 53–387% in Eln −/−, Lox −/−, and Fbln4 −/− aorta, indicating that not only elastin, but properly assembled and crosslinked elastic fibers, are necessary for low energy loss in the aorta.